2023
DOI: 10.1038/s41598-023-27957-x
|View full text |Cite
|
Sign up to set email alerts
|

Under-ice observations by trawls and multi-frequency acoustics in the Central Arctic Ocean reveals abundance and composition of pelagic fauna

Abstract: The rapid ongoing changes in the Central Arctic Ocean call for baseline information on the pelagic fauna. However, sampling for motile organisms which easily escape vertically towed nets is challenging. Here, we report the species composition and catch weight of pelagic fishes and larger zooplankton from 12 trawl hauls conducted in ice covered waters in the Central Arctic Ocean beyond the continental slopes in late summer. Combined trawl catches with acoustics data revealed low amounts of fish and zooplankton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
1
0
0
Order By: Relevance
“…4E). An increased influence of the Barents Sea may cause the eastern Eurasian Basin to be more productive and provide more suitable living conditions for subarctic-boreal species than its western part ( 51 ), which is consistent with recent observations ( 50 ). Improved knowledge of asymmetric conditions in the pelagic ecosystems of the western and eastern Eurasian Basin is imperative to properly understand and manage the central Arctic Ocean fisheries agreement established in 2021.…”
Section: Discussionsupporting
confidence: 91%
“…4E). An increased influence of the Barents Sea may cause the eastern Eurasian Basin to be more productive and provide more suitable living conditions for subarctic-boreal species than its western part ( 51 ), which is consistent with recent observations ( 50 ). Improved knowledge of asymmetric conditions in the pelagic ecosystems of the western and eastern Eurasian Basin is imperative to properly understand and manage the central Arctic Ocean fisheries agreement established in 2021.…”
Section: Discussionsupporting
confidence: 91%
“…finmarchicus , and Oithona spp. This is in line with morphological studies in the same area (Darnis & Fortier, 2014; Gluchowska, Dalpadado et al., 2017; Ingvaldsen et al., 2023; Kosobokova et al., 2011), as well as findings in the Chukchi Sea (Questel et al., 2021). We recovered sequences from holoplanktonic (e.g., physonect siphonophores and calanoid copepods) and benthic taxa (e.g., bryozoans and polychaete worms), including many with meroplankton life stages (e.g., echinoderms and poriferans).…”
Section: Discussionsupporting
confidence: 87%
“…They serve major ecosystem roles as predators and are important in pelagic-benthic coupling and vertical carbon export (Jaspers et al, 2023;Lebrato et al, 2012Lebrato et al, , 2013, particularly when occurring in high numbers (aggregations or blooms). Recent studies have shown poleward expansions of the distribution ranges of boreal species, e.g., for the large scyphozoan Periphylla periphylla around Svalbard and in the Nansen Basin (Geoffroy et al, 2018;Ingvaldsen et al, 2023). Additionally, increased abundances of the arcto-boreal hydrozoan Aglantha digitale have been found in warmer water masses in the North Atlantic (Haberlin et al, 2019) and in Atlantic water masses in Fram Strait (Mańko et al, 2020), where it is predicted to become a dominant species as the Arctic warms (Mańko et al, 2020;Pantiukhin et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%